Enantioselective synthesis of spirocyclohexadienones by NHC-catalyzed formal [3+3] annulation reaction of enals - Yetra, Santhivardhana Reddy; Mondal, Santigopal; Mukherjee, Subrata; Gonnade, Rajesh G.; Biju, Akkattu T. (Angewandte Chemie-International Edition, 2016)
The enantioselective synthesis of pyrazolone-fused spirocyclohexadienones was demonstrated by the reaction of alpha,beta-unsaturated aldehydes with alpha-arylidene pyrazolinones under oxidative N-heterocyclic carbene (NHC) catalysis. This atom-economic and formal [3+3] annulation reaction proceeds through a vinylogous Michael addition/spiroannulation/dehydrogenation cascade to afford spirocyclic compounds with an all-carbon quaternary stereocenter in moderate to good yields and excellent ee values. Key to the success of the reaction is the cooperative NHC-catalyzed generation of chiral alpha,beta-unsaturated acyl azoliums from enals, and base-mediated tandem generation of dienolate/enolate intermediates from pyrazolinones.
Keywords: annulation reactions; asymmetric catalysis; N-heterocyclic carbenes; organocatalysis; spiro compounds

N-Heterocyclic carbene-catalyzed aldol-lactonization of ketoacids via dynamic kinetic resolution - Mondal, Santigopal; Mukherjee, Subrata; Das, Tamal Kanti; Gonnade, Rajesh; Biju, Akkattu T. (ACS Catalysis, 2017)
N-Heteroryclic carbene (NHC)-catalyzed enantioselective aldol lactonization of acyclic ketoacids, proceeding via dynamic kinetic resolution, is presented. The carbene generated from the chiral anninoinclanol-derived triazolium salt in the presence of LiCl was the key for the success of this transformation. The reaction allowed the diastereoselective and enantioselective synthesis of cyclopentane-fused beta-lactones having three contiguous stereocenters. The reaction products are shown to undergo substrate-controlled beta-lactone opening in the presence of amines to afford succinimide derivatives with four contiguous stereocenters.
Keywords: aldol lactonization; beta-lactones; DKR strategies; ketoacids; N-heterocyclic carbenes; organocatalysis